2019
DOI: 10.1177/0961203319843343
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine treatment during pregnancy in lupus patients is associated with lower risk of preeclampsia

Abstract: Background Hydroxychloroquine (HCQ) is regarded as a mainstay in the treatment of systemic lupus erythematosus (SLE) because of its efficacy in preventing flares, achieving remission, and reducing overall mortality. However, the impact of HCQ on pregnancy outcomes remains controversial. Objective We aimed to investigate the effect of HCQ on pregnancy outcomes in patients with SLE. Methods We performed a retrospective cohort study of 151 pregnancies in 122 patients with SLE (80 pregnancies in the HCQ treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 41 publications
6
84
2
5
Order By: Relevance
“…Our results support recent information about antimalarial drugs reducing the risk of developing preeclampsia in women with SLE. 29 On the other hand, active disease before and during pregnancy is associated with an increased risk of developing preeclampsia, as it has been previously reported. 32,[34][35][36][37][38][39] In fact some of these angiogenic factors are potential biomarkers for predicting preeclampsia in patients with SLE and APS, such as endoglin, sFlt-1 and PIGF, because these factors are progressively elevated in patients who are complicated with preeclampsia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our results support recent information about antimalarial drugs reducing the risk of developing preeclampsia in women with SLE. 29 On the other hand, active disease before and during pregnancy is associated with an increased risk of developing preeclampsia, as it has been previously reported. 32,[34][35][36][37][38][39] In fact some of these angiogenic factors are potential biomarkers for predicting preeclampsia in patients with SLE and APS, such as endoglin, sFlt-1 and PIGF, because these factors are progressively elevated in patients who are complicated with preeclampsia.…”
Section: Discussionmentioning
confidence: 76%
“…For the analysis, each pregnancy was con- The sample size calculation was performed based on the results of a recently published study that found that 7.5% of patients exposed to hydroxychloroquine developed preeclampsia compared to 19.7% in those unexposed patients. 29 With these data, using an alpha error of 0.05 and a beta error of 0.2, a minimum of 196 pregnancies were obtained to have a statistical power of 80%. The multivariate analysis with binary logistic regression was performed to identify potential independent risk factors for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…The pregnancy duration was longer for HCQ‐treated women (27.6 vs. 21.5 weeks; P = 0.03), and the new‐born birth weight was higher (3 kg vs. 2.3 kg; P = 0.04). Similarly, a retrospective Chinese study of 152 pregnancies in 122 women with SLE reported an 89% reduction in PE in HCQ‐treated women vs. non‐HCQ‐treated women …”
Section: Clinical Studies On Hcq In Rm and Ementioning
confidence: 93%
“…Our finding that HCQ decreases the risk of preeclampsia is consistent with a recently published retrospective cohort study of 151 SLE pregnancies managed at a single institution from 1995 to 2018. 11 Seo et al showed that preeclampsia was significantly less common in the HCQ treatment group (19.7 vs. 7.5%; p ¼ 0.032). Our study provides further evidence supporting the protective effect of HCQ against preeclampsia.…”
Section: Discussionmentioning
confidence: 97%
“…[8][9][10] Emerging evidence suggests that HCQ may reduce the risk of preeclampsia. 11 Preeclampsia affects up to 30% of SLE pregnancies compared with 3.4% of pregnancies in the United States overall. [12][13][14][15][16] Preeclampsia increases maternal risks of stroke, renal failure, hepatic failure, and death.…”
mentioning
confidence: 99%